The Consumption Function Model of Coastal Communities in South Kalimantan based on the Use of Digitalization in Maslahat Perspective - Faulidi Asnawi, Haris; Purnomo, Agus; Asyahri, Yusuf; Khaliq, Restu (Tasharruf: Journal Economics and Business of Islam, 2024)
The development of the Industrial Revolution 4.0 and the progress of the times in the era of Society 5.0 give an idea that information technology has entered various lines of people's lives so that the government encourages people to use the payment digitization system as a form of accelerating the push for economic and financial instruments in Indonesia. Many digitization systems are provided through non-cash payment instruments, one of which is Gopay, OVO, Mobile Banking, and Digital Wallets. The purpose of this research is to form a model of the pattern of public consumption approach based on the use of digitalization and also how the function of maslahah and the description of the digitalization of coastal communities. This study uses field methods and surveys. The sample used was respondents who used e-money in coastal communities with a total of 60 respondents determined based on the sampling quota. Then, it was analyzed using the Keynes consumption function model in macro terms and the consumption function in benefits. The results show that the consumption function model of coastal communities based on the use of digitalization is C = 539,487 + 0.17 Y with an Average Propensity to Consume (APC) value of 0.99 while APS is 0.01 while the Marginal Propensity To Consume Value = 0.17 and the Marginal Propensity To Saving Value= 0.83. Meanwhile, for the consumption function model, the use of digitalization in the perspective of benefits can be shown by the results Y = 3.368 + 0.725 C + 0.017 S + 0.064 X and for the value of Y = FS + S is Y = 2.853 + 0.775 FS + 0.065 S.